Study of Coral Reef Distribution in Pejarakan Waters, Bali Using Sentinel-2A Imagery - Bambang Semedi; Seftiawan Samsu Rijal; Dhika Anggi Arviani (Jurnal Perikanan dan Kelautan, 2024)
The existence of coral reef ecosystems in Indonesia is a potential marine resource that needs to be preserved due to the many benefits of the coral reef ecosystem. Utilization of Sentinel-2A imagery for coral reef mapping can be done using two approaches, namely pixel-based and object-based. In this study, pixel-based classification and object-based classification are used to determine the dynamics of the distribution of coral reefs in the waters of Pejarakan Village, Bali, during the dry and rainy seasons. The data used are Sentinel-2A image data for 2018, 2020, and 2022 and field data used for the research accuracy test process. Field data was collected using the purposive sampling method, and the accuracy test process was carried out using the confusion matrix method. The data processing results using pixel and object classification show that classification using the object classification method is considered more accurate than pixel classification because it produces an accuracy value of up to 69.4%. Meanwhile, the pixel classification accuracy value is only 61.1%.